العلاقة بين الكفاءة الذاتية للمديرين التربويين وفاعلية إدارة الأزمات في البيئة التعليمية (Comprehensive Journal of Science, 2025)
This research employed a descriptive-analytical approach and a systematic literature review of 56 studies published between 2015-2025 to explore the relationship between educational leaders' self-efficacy and their effectiveness in crisis management within educational settings. The study's significance arises from the critical need to understand the educational leadership's role in facing contemporary challenges, thereby supporting the development of training programs and selection of effective leaders to ensure educational continuity and quality. The objectives were to identify the levels of both variables as presented in the reviewed literature, and to investigate the nature and related aspects of their relationship. Data extracted from the studies were analyzed using thematic analysis. Findings showed a strong positive correlation between self-efficacy and crisis management effectiveness (R=0.723), with self-efficacy tangibly contributing (38.3%) to enhancing effectiveness. Results also underscored the importance of transformational and proactive leadership and the influence of contextual factors. The study recommends incorporating self-efficacy in leader selection, developing targeted training, fostering supportive environments, and conducting future research in diverse contexts using integrated (longitudinal/mixed) methodologies.
Keywords: Self-efficacy, Crisis Management, Educational Leaders, Educational Environment.